DIAGNOSTIC AND PROGNOSTIC SIGNIFICANCE OF MICROBIAL FLORA IMBALANCE IN GINGIVAL BIOFILM - Loban, G. A.; Petrushanko, T. O.; Chereda, V. V.; Faustova, M. O.; Ananieva, M. M.; Basarab, Ya. A. (International Journal of Medicine and Medical Research, 2020)
Background. Periodontal tissues inflammatory diseases are widespread among young people. Objective. This study was aimed at elaborating the method to assess risks of periodontal inflammatory diseases and determining its efficacy depending on the state of dental tissues, gum tissues and sex. Methods. The study included 182 students (93 men, 89 women) aged 19-29: 22 individuals had no lesions of hard dental tissues and no signs of periodontal disease; 51 individuals were found to have DMF index <6; 52 individuals – DMF index ≥6; 57 individuals were diagnosed with chronic catarrhal gingivitis. Primary groups were formed in autumn; re-examination was carried in spring. The research participants were assessed for detection of risks of periodontal inflammatory disease by the method developes by the authors (Patent UA 54041). Results. The study revealed that the risk of development of preiodontitis increases in individuals with high caries and gingivitis intensity. In spring, more individuals suffer from microbial imbalance in in the composition of gingival sulcus fluid and decrease in the mean stability coefficient value that indicates an increased risk of inflammatory periodontal disease development. Women were less likely to experience seasonal dysbiotic changes in the gingival sulcus fluid composition compared with men. Conclusions. The method suggested for assessment of the risk of periodontal inflammatory diseases is of high informativeness. It allows clinicians detecting early pre-nosological signs of oral microbiocenosis imbalance that enhances the effectiveness of early diagnosis of inflammatory periodontal diseases.